Pengaruh Pemberian Edukasi Video Gizi Seimbang terhadap Preferensi Makanan pada Remaja Awal di SMP Widya Manggala Jakarta Timur - Yudha Putra Erlangga; Ahmad Faridi; Mohammad Furqan (Jurnal Kesehatan Indonesia, 2025)
Watching mukbang videos has become a popular habit nowadays, especially among teenagers and adults. This trend is supported by the ease of internet access and the wide variety of mukbang videos available on social media, attracting many fans, particularly college students. The presentation of food and the act of eating in mukbang videos provide visual stimuli that can influence viewers' food choices. The presentation of food and the act of eating in mukbang videos provide visual stimuli that can influence viewers' food choices. This study aims to analyze the effect of providing education through balanced nutrition mukbang videos on food preferences among early adolescents. The research employs a quantitative method with a quasi-experimental pre-post test design. Sampling was conducted using a random sampling method. The sample consisted of 36 early adolescents. The educational media used was a balanced nutrition educational video created by the researchers. The statistical test employed in this study was the Paired T-Test test. The results of the study showed that, prior to the education intervention, 67.5% of adolescents had a preference for unbalanced nutrition, while 32.5% preferred balanced nutrition, based on the score category. After the education intervention, 27.5% of adolescents still preferred unbalanced nutrition, whereas 72.5% preferred balanced nutrition. Bivariate analysis indicated that there was a significant effect of the balanced nutrition video education on food preferences (p = 0.00).